ANALYSIS OF TEMBILAHAN PUBLIC UNDERSTANDING OF FINANCIAL TECHNOLOGY AND HOW FINANCIAL TECHNOLOGY-BASED INSURANCE SERVICES WORK - Fitri Ramadhani; Rini Aulia; Syarif Lovedly (Indragiri Research Center (ingreat), 2025)
The development of financial technology (fintech) has driven innovation in financial services, including fintech-based insurance services (InsurTech). However, utilization of these services still faces obstacles in the form of low public understanding, particularly in non-metropolitan areas. This study aims to analyze the Tembilahan community's understanding of fintech and how fintech-based insurance services work, and to identify the factors influencing it. This study used a qualitative method with a descriptive approach. Data were obtained through in-depth interviews with Tembilahan residents selected using purposive sampling. The results indicate that the community generally only understands fintech as a digital payment service and does not yet understand the mechanisms. Service digital insurance. Low digital financial literacy, limited information, and perceived risks regarding data security and the claims process are the main factors contributing to this low understanding. However, after being provided with an explanation, the public showed a more positive attitude toward digital insurance services. Therefore, increasing digital financial literacy and education is necessary to encourage optimal understanding and utilization of insurance fintech.